Pengembangan Kawasan Pertanian Berbasis Tanaman Pangan di Kecamatan Wuluhan, Kabupaten Jember - Eli Fatul Laili; Herman Cahyo Diartho (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2018)
This study aims to understand the base commodities of food crops in agricultural sector development at Wuluhan District, Jember Regency, to understand the distribution of agricultural support facilities in each village, and to determine strategies for food crop-based agriculture area development at the area. This research is a quantitative descriptive research with analysis conducted in 2011-2015 using Location Quotient, Scalogram and SWOT analysis techniques. Location Quotient analysis results show that base commodities during 2011-2015 are corn and sweet potato. Scalogramresults show that Wuluhan District has agricultural facilities and infrastructures in the criteria ofhierarchy III and hierarchy IV. Based on the results of SWOT analysis on leading commodities of the food crop subsector in Wuluhan District, the development strategy is in quadrant I or is an aggressivestrategy. Aggressive strategy in this study is used as a strength in utilizing opportunities from region’s potential in order to develop agricultural areas through the role of farmers or farmer groups’ institution, farmer business credit, human resources, and mutual cooperation systems for rice fieldwatering or irrigation.